2008
DOI: 10.1245/s10434-008-9809-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics and Prognosis for Young Gastric Adenocarcinoma Patients after Curative Resection

Abstract: The predominance of female cases and tumors that were histologically undifferentiated were distinctive characteristics in young patients. Young patients could gain a survival benefit after curative resection with stage I disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 20 publications
7
34
3
1
Order By: Relevance
“…In the AGC group, there were a significantly higher proportion of T4 and stage IV patients in the young age group. However, recent reports based on surgically resected patients from our institution showed that the proportions of T4, N3, and stage IV were similar between young and elderly patients [17]. This discrepancy is due to the inclusion of surgical unresectable patients (i.e., more advanced cases) in our study.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In the AGC group, there were a significantly higher proportion of T4 and stage IV patients in the young age group. However, recent reports based on surgically resected patients from our institution showed that the proportions of T4, N3, and stage IV were similar between young and elderly patients [17]. This discrepancy is due to the inclusion of surgical unresectable patients (i.e., more advanced cases) in our study.…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, several studies have shown that the 5-year survival rate does not differ significantly between young and elderly patients [21,22]. In a few reports, including our surgical study [17,23], the prognosis for young patients who undergo curative resection is better than that of older patients. In this study, although curative resection and resectability rate was lower in young patients (Table IV), if curatively resected, the overall survival rate of young patients was significantly higher than that of older patients.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 64%
“…About half of the patients were diagnosed as SRC, and there were slight female predominance. Previous studies have reported young age GC shows slight female predominance or similar prevalence between both sexes, with higher rate of poorly differentiated carcinoma or SRC by pathologic review [4,5,14]. Previously mentioned clinical characteristics were in concordance to studies mentioned above.…”
Section: Discussionsupporting
confidence: 85%
“…In Western studies, the prevalence of AGCa is by far higher than EGCa [6,10]. Compared to Western, the prevalence of AGCa and EGCa were similar in Asian studies [4,5,14], alike to our analysis. This discrepancy may be due to different screening program between Western and Asia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation